Pengaruh Framing Terhadap Penggunaan Teknologi Pengelolaan Keuangan Pada UMKM di Banyumas - Primasari, Dona; Herwiyanti, Eliada; Widianingsih, Rini (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The inability of accounting, which includes recording techniques for transaction processes and the use of software, has failed of MSMEs in developing their businesses. This study examines the effect of positive and negative framing on the use of technology-based financial software. Data collection in this study was conducted by distributing questionnaires as many as 100 questionnaires with purposive sampling technique, a total of 98 questionnaires that can be processed. Data analysis using Statistical Product and Service Solution (SPSS) version 22.0. The results provide empirical evidence that the concept of positive framing and negative framing affects the use of technology-based financial software. for MSME actors, as well as supporting the prospect theory concept used in research. Keywords: framing, prospect theory, financial management, financial software, MSMEs